Brand image analysis of Indonesian telecommunication company: A quantitative approach - Dumasari, Nadhifah; Pradana, Mahir; Rintaningrum, Ratna; Musa, Hussein Gibreel; Syarifuddin, Syarifuddin (Edelweiss Applied Science and Technology, 2025)
Social media has become an essential marketing tool for companies to establish and maintain their brand image, with Instagram offering a highly effective platform due to its visual and interactive features. This research aims to explore how strategic elements such as content creativity, consistency, and user engagement influence the brand image of Indonesian Telekomunikasi (PT INTI). A quantitative approach was utilized, with data collected through a questionnaire distributed to 458 respondents, all of whom were familiar with the @ptintiofficial Instagram account. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Based on our findings, recommendations are provided to optimize PT INTI’s Instagram strategy, such as improving user interaction, ensuring consistent posting schedules, and utilizing innovative Instagram features. This study contributes to understanding the role of social media in shaping brand image and offers practical insights for PT INTI and other organizations aiming to strengthen their branding via Instagram. Future research is encouraged to investigate additional variables and employ diverse methodologies to broaden the scope of this topic.